2009
DOI: 10.1074/mcp.m800428-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Scoring of Protein Interaction Subnetworks Discriminative of Late Stage Human Colon Cancer

Abstract: We used a systems biology approach to identify and score protein interaction subnetworks whose activity patterns are discriminative of late stage human colorectal cancer (CRC) versus control in colonic tissue. We conducted two gel-based proteomics experiments to identify significantly changing proteins between normal and late stage tumor tissues obtained from an adequately sized cohort of human patients. A total of 67 proteins identified by these experiments was used to seed a search for proteinprotein interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 36 publications
1
91
0
Order By: Relevance
“…Nonetheless, this approach has already been proved to be effective for the identification of complex disease genes, including those involved in colon cancer (Nibbe et al, 2009). Therefore, analyzing the functional networks of human genes is providing a key framework for prioritizing candidate disease genes.…”
Section: Network Studies To Leverage Functional Predictionmentioning
confidence: 99%
“…Nonetheless, this approach has already been proved to be effective for the identification of complex disease genes, including those involved in colon cancer (Nibbe et al, 2009). Therefore, analyzing the functional networks of human genes is providing a key framework for prioritizing candidate disease genes.…”
Section: Network Studies To Leverage Functional Predictionmentioning
confidence: 99%
“…Integrating PPI networks with expression data, for example, led to the identification of cancer susceptibility genes and oncogenes in breast carcinomas [122], B-cell acute myeloid lymphomas [123,124]; the identification of markers for metastasis in breast [125,126], colorectal [127,128] and gastric [129] cancer; the prediction of disease outcome [130] and response to chemotherapy [131,132] and the determination of therapy-resistance genes [133,134]. By combining protein-protein and protein-DNA interaction studies Kim et al identified a Myc-centered regulatory network in embryonic stem cells, and showed that the Myc module is active in various cancers and predicts cancer outcome [135].…”
Section: Disease Disease Gene or Pathway Referencementioning
confidence: 99%
“…Subnetworks identified by this approach are also used as features for classification of breast cancer metastasis, providing significant improvement over single-gene markers [20]. Nibbe et al [21,22] show that this notion of coordinate dysregulation is also effective in integrating protein and mRNA expression data to identify important subnetworks in colon cancer (CRC). Anastassiou [23] introduces the concept of synergy to delineate the complementarity of multiple genes in the manifestation of phenotype.…”
Section: Introductionmentioning
confidence: 99%